PM.36 Resource Implications of Converting from a WHO/ADA Hybrid to IADPSG Criteria For Diagnosing GDM in a UK University Hospital. (26th April 2013) - Anthony, R; Angala, P; Ikomi, A; Khan, R; Kiss, S
Abstract : Background: In the UK, two studies have reported discordant findings in predicting the impact of International Association of the Diabetes and Pregnancy Study Group (IADPSG) criteria on the number of GDM cases (3% vs. 114% increase). This disparity warrants further evaluation. Our unit offers a 3 point GTT utilising the WHO thresholds for fasting and 2 hrs, American Diabetes Association (ADA) threshold for 1 hr and like the IADPSG requires only one criterion for a positive diagnosis. Our unique access to this type of OGTT data makes us well placed to forecast the minimum impact on services. Aims: To ascertain the number of women diagnosed as GDM using WHO, WHO/ADA and IADPSG criteria. To determine the resource implications of IADPSG criteria. Methods: A retrospective study of 2905 OGTT results of women delivered in our unit between 1st January 2009 and 31st December 2011. Results: The numbers of women diagnosed with GDM were 327, 454 and 528 using WHO, WHO/ADA and IADPSG criteria respectively. This shows IADPSG criteria would lead to a 16.3% increase in our number of GDM cases equating to 25 extra cases/year. Had we been reliant on just WHO criteria, adopting IADPSG criteria would lead to a 61.4% increase, equating to 67 extra cases/year. Conclusions: UK units offering a 2 point WHO GTT should expect a > 60% increase in GDM numbers with IADPSG implementation. On the contrary, units already offering a 3 point WHO/ADA hybrid should anticipate a less drastic 16% increase.